Pengaruh Persepsi Harga, Kualitas Pelayanan dan Lokasi Terhadap Kepuasan Pelanggan di Bengkel Body Repair CK Motor Purbalingga - Ragil Danu Saputra; Arini Hidayah; M Agung Miftahudin; Maulida Nurul Innayah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to analyze the impact of price perception, service quality, and location on customer satisfaction at CK Motor Body Repair Workshop in Purbalingga. This research employs a quantitative approach with a questionnaire as the primary data collection tool. The sample consists of 113 customers of CK Motor Body Repair Workshop in Purbalingga, selected using purposive sampling with the criteria: 1) having used the services of CK Motor Body Repair Workshop at least twice, and 2) having an income. Data analysis was performed using multiple linear regression techniques with SPSS version 25. The findings indicate that 1) price perception has a positive and significant effect on customer satisfaction, 2) service quality has a positive and significant effect on customer satisfaction, and 3) location does not affect customer satisfaction. Therefore, CK Motor Body Repair Workshop should focus on offering appropriate pricing and improving service quality to enhance customer satisfaction. Location does not need to be a primary concern, allowing the workshop to redirect attention and resources towards improving pricing and service aspects that are crucial for customer satisfaction.